Renewable energy sources: global implementation experience - Nazarov Anton; Sulimin Vladimir; Shvedov Vladislav (E3S Web of Conferences, 2024)
The imperative transition towards renewable energy sources is a global challenge with diverse implementation experiences. This paper provides a comprehensive review of the worldwide deployment of renewable energies, examining case studies from different geographic and economic contexts to assess methods, outcomes, and lessons learned. It delves into the advancements in solar, wind, hydroelectric, and geothermal energy, showcasing innovative technologies and strategies that have significantly contributed to the energy mix. We analyze policy frameworks, investment patterns, and community engagement practices that have facilitated the adoption of renewables. Additionally, the paper explores the barriers to implementation, including economic, technical, and political challenges, and suggests pathways for overcoming these hurdles. Comparative analysis of the effectiveness of different renewable projects highlights the importance of tailored approaches that consider local conditions. The paper concludes with strategic recommendations for policymakers, industry stakeholders, and researchers to promote the global expansion of renewable energy sources, aiming for sustainability and energy security.